Exploration of crystal growth behavior in Au-based metallic glass by nanocalorimetry. (April 2022) - Xiao, Huan; Zhang, Li; Yi, Jun; Li, Shun; Zhao, Bingge; Zhai, Qijie; Gao, Yulai
Abstract: The Au49 Ag5.5 Pd2.3 Cu26.9 Si16.3 (at.%) bulk metallic glass is among the promising Au-based metallic glasses with the enhanced glass-forming ability and thermal stability. However, crystal growth kinetics during the crystallization of this metallic glass remains ambiguous. In this study, the rapid crystallization of a Au49 Ag5.5 Pd2.3 Cu26.9 Si16.3 bulk metallic glass in a wide temperature range was realized by nanocalorimetry. The underlying thermodynamic and kinetic features of crystal growth were ascertained based on the Cohen and Grest (C&G), Mauro-Yue-Ellison-Gupta-Allan (MYEGA) and Schmelzer models, and the adaptability of these three models was demonstrated. The maximum crystal growth rate (0.037 m/s) and corresponding temperature (595 K) estimated by these three models were similar but different crystal growth behaviors in the deeply undercooled melt were distinguished. With an increase in undercooling, the breakdown of the Stokes-Einstein relation was discovered, and a temperature-dependent decoupling exponent was demonstrated by the Schmelzer model, causing a divergence of crystal growth rate from that estimated by C&G and MYEGA models. Moreover, screw-dislocation-mediated growth was stated as the dominant crystal growth mechanism during the crystallization of the Au49 Ag5.5 Pd2.3 Cu26.9 Si16.3 bulk metallic glass. Highlights: Crystal growth rate from T g to T m is told by C&G, MYEGA, and Schmelzer models. These models predict similar maximum growth rate and corresponding temperature. Crystal growth rate can be better depicted with temperature-dependent decoupling. Screw-dislocation-mediated growth is the dominant crystal growth mechanism.